ICCCE 2018 Proceedings of the International Conference on Communications and Cyber Physical Engineering 2018 - Kumar, Amit; Mozar, Stefan (Lecture Notes in Electrical Engineering, 2019)
This book comprises selected articles from the International Communications Conference (ICC) 2018 held in Hyderabad, India in 2018. It offers in-depth information on the latest developments in voice-, data-, image- and multimedia processing research and applications, and includes contributions from both academia and industry.